The Effect of MSE’s Understanding Toward Consumer’s Psychological Factors in Implementing Promotional Strategies - Dimas Perdana Oskar; Mirsal; Andhika Anggawira (International Journal of Social Science and Business, 2023)
Most micro and small-scale entrepreneurs face difficulties in scaling their business even though they have a great product. This study aims to understand the understanding of micro and small enterprises (MSEs) in Padang City about consumer psychology and how this understanding can be used in developing effective and efficient promotional strategies in the digital era. The research design is descriptive research on secondary data to determine the influence of understanding MSE actors in Padang City on consumer psychological factors in implementing promotional strategies both partially and simultaneously. The purposive sampling approach with a 10% margin of error using Isaac and Michael's theory was tested against 253 samples and measured by a Likert scale questionnaire collected from June 2022 to August 2022. The results of the validity test on 97 respondents showed that the consumer psychology variable consisting of 30 statements produced an R of 0.910 while the promotion strategy variable with 14 statements produced an R of 0.839. It was concluded that both simultaneously and partially there was no influence where Micro and Small Enterprises understood the psychology of consumers in developing promotional strategies. The implication of this research is that business actors, especially MSEs, need to understand the importance of digital media marketing in reaching customers in a personalized and relevant way.